2017
DOI: 10.1097/qai.0000000000001273
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Experiences of Women and Health Care Workers in the Context of PMTCT Option B Plus in Malawi

Abstract: Introduction Malawi has embarked on a ‘test-and-treat’ approach to prevent mother-to-child transmission of HIV (PMTCT), known as ‘Option B+’, offering all HIV-infected pregnant and breastfeeding women lifelong antiretroviral treatment (ART) regardless of CD4-count or clinical stage. We conducted a cross-sectional qualitative study to explore early experiences surrounding ‘Option B+’ for patients and health care workers (HCWs) in Malawi. Methods Study participants were purposively selected across six health f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 14 publications
9
72
0
Order By: Relevance
“…This also compounded the struggle with stigma and discrimination as some women would choose to protect their relationships through leverage of husbands' absence at Antenatal care and cultural practices that would raise ag in mothers do not breastfeed the child. Similar results were reported elsewhere (38) as their main nding in Malawi and Uganda populations and in Malawi (41). Poverty as a barrier reported here has also been reported by other studies as lack of funds to travel for Antenatal care (37,40).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This also compounded the struggle with stigma and discrimination as some women would choose to protect their relationships through leverage of husbands' absence at Antenatal care and cultural practices that would raise ag in mothers do not breastfeed the child. Similar results were reported elsewhere (38) as their main nding in Malawi and Uganda populations and in Malawi (41). Poverty as a barrier reported here has also been reported by other studies as lack of funds to travel for Antenatal care (37,40).…”
Section: Discussionsupporting
confidence: 91%
“…Stigma and discrimination is reported as a major barrier across studies and countries and it was reported as a major issue by the participants including internalized stigma (35,37,38,40,41). Despite, information on HIV be widely available through all media, this study con rmed that stigma and discrimination are still a major issue in HIV in Ethiopia and in other African states stigma (35,37,38,40,41)). Unlike ndings from Schechter et al (40) stigma in Amhara region is not largely internalized but rather from the community and sometimes health care professionals.…”
Section: Discussionmentioning
confidence: 54%
“…However, very early on, some women identified as HIV-positive in pregnancy and instructed to start ART for life were reluctant and rather than refuse treatment, disposed of the ARVs (based on anecdotal stories from implementing partners' observations). A recent presentation suggested that stigma, confidentiality, privacy, and the method of initiating ART continue to challenge PMTCT services in Malawi (Cataldo et al 2013).…”
Section: Site Performance Variationsmentioning
confidence: 99%
“…PMTCT care as well as ART to prevent sexual transmission, condom use, and voluntary male medical circumcision are successful strategies for HIV prevention in low and middle-income countries [2,3,12]. However, qualitative evidence from sub-Saharan Africa (SSA) and Asia has shown that concerns about unintentional HIV status disclosure and HIV related stigma are barriers to participate in PMTCT care among pregnant women [13][14][15][16][17][18]. Qualitative studies have also identified other important barriers to HIV status disclosure including concerns about separation or divorce [19][20][21][22][23], conflicts with a partner [19,21], intimate partner violence (IPV) [19][20][21]23] and stigma in the family or community [20,23].…”
Section: Introductionmentioning
confidence: 99%